"Emotional Darkness without Solutions": Subjective Experiences of Mental Health Crisis. Issue 3 (2nd July 2016) - Gullslett, Monika K.; Kim, Hesook Suzie; Andersen, Anders J. W.; Borg, Marit
Abstract: The purpose of this study is to explore and describe service users' subjective experiences of mental health crisis. The main research question is: How do people with severe mental health problems experience and understand mental health crisis? Based on a hermeneutic-phenomenological methodology, in-depth interviews with seven participants have been carried out to encourage reflections on mental health crisis experiences. The findings reveal the crisis as being complex and multifaceted, which contains two dimensions in experiencing crisis—an existential dimension (personal) and a contextual (social) dimension. Three main themes identified through the analysis, "Feeling out of control, " "Emotional darkness, " and "Loneliness and seeking togetherness". Mental health crisis is experienced as chaos, losing control, loss of energy, and feelings of hopelessness. During mental health crisis, one's social life can be difficult and involve many paradoxes and daily challenges. However, the participants revealed an understanding of a need for help, as mental health crisis emerges as a continuity of struggles in complex situations. There is a need for more comprehensive and broader perspectives of mental health crisis as a phenomenon, especially from the person's perspective. Conceptualizing mental health crisis experiences from the person-perspective offers an opportunity for understanding this as an integral part of people's lives. The nature of mental health crisis explicitly captured and understood in light of the complexity of personal lives is critical in developing recovery-oriented mental health care.